INFLUENCE OF WORK DISCIPLINE, LEADERSHIP STYLE AND COMPETENCE TO PERFORMANCE STATE CIVIL APPARATUS - Badri, Juarsa; Monika, Monika (LPPM Universitas Bina Bangsa, 2022)
This study aimed to determine and analyze the effect of work discipline, leadership style, and competence on the performance of the State Civil Apparatus in Lubuk Begalung Sub-District Padang. The population in this study were all State Civil Apparatus in Lubuk Begalung Sub-District Padang, totaling 84 people. The sampling technique used is saturated sample. Because the population in this study was relatively small, and less than a hundred people, the entire population could be sampled. The data analysis technique used to test the hypothesis is the statistical t test. The results showed that work discipline affects employe performance. This is because work discipline has a significant value of 0.000, this significant value is smaller than alpha 0.05. This means that work discipline has a significant effect on employe performance. Leadership style does not affect employe performance. This is because leadership style has a significant value of 0.297, which is greater than alpha 0.05. This means that leadership style has no significant effect on employe performance. Competence affects employe performance. This is because competence has a significant value of 0.018, this significant value is smaller than alpha 0.05. This means that competence has a significant effect on employe performance